2014
DOI: 10.1007/s11999-014-3614-x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Deep Vein Thrombosis After Periacetabular Osteotomy in Adult Patients: Is It Necessary?

Abstract: Level IV, therapeutic study. See the Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…They found a 1.3% rate of deep venous thrombosis on routine screening of 136 hips, with a mean patient age of 30 years. 27 In adolescents undergoing periacetabular osteotomy, Thawrani et al 28 found no cases of symptomatic deep venous thrombosis in a cohort of 83 patients. The current study reports a thromboembolic disease rate of 2 of 75 (2.67%) in patients receiving aspirin twice daily as well as mechanical prophylaxis after undergoing Bernese periacetabular osteotomy with intravenous tranexamic acid.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They found a 1.3% rate of deep venous thrombosis on routine screening of 136 hips, with a mean patient age of 30 years. 27 In adolescents undergoing periacetabular osteotomy, Thawrani et al 28 found no cases of symptomatic deep venous thrombosis in a cohort of 83 patients. The current study reports a thromboembolic disease rate of 2 of 75 (2.67%) in patients receiving aspirin twice daily as well as mechanical prophylaxis after undergoing Bernese periacetabular osteotomy with intravenous tranexamic acid.…”
Section: Discussionmentioning
confidence: 97%
“…Zaltz et al 6 reported on the crude incidence of deep venous thrombosis and pulmonary embolism in adult and adolescent patients undergoing Bernese periacetabular osteotomy and found a low rate of 9.4 of 1000 with variable anticoagulation protocols. Polkowski et al 27 studied the frequency of thromboembolic disease in adult patients undergoing periacetabular osteotomy and receiving aspirin twice daily as well as mechanical prophylaxis by assessing an ultrasound at 1 week postoperatively. They found a 1.3% rate of deep venous thrombosis on routine screening of 136 hips, with a mean patient age of 30 years.…”
Section: Discussionmentioning
confidence: 99%
“…Polkowski et al [ 55 ], in a retrospective cohort, indicated that the risk of symptomatic DVT associated with PAO is low (1%) with use of aspirin 325 mg two times daily along with mechanical compression prophylaxis for 6 weeks. Furthermore, routine post-operative screening did not detect any patients with an asymptomatic DVT.…”
Section: Current Evidences Regarding Prevention Of Vte After Hpsmentioning
confidence: 99%
“…They reported an overall incidence of VTE to be 0.94%. Polkowski et al studied the frequency of thromboembolic disease in adult patients undergoing PAO and receiving aspirin twice daily as well as mechanical prophylaxis by assessing an ultrasound at 1 week post-operatively [ 3 ]. They found a 1.3% rate of DVT on routine screening of 136 hips, with a mean patient age of 30 years (range 18–60 years).…”
Section: Discussionmentioning
confidence: 99%